Multi-format video frame grabber imageJ plugin : MVFG - Laranjo, Isabel (2012)
Currently ImageJ presents itself as a good working tool for medical imaging research. Image processing and analysis using specific ImageJ plugins is a simple process, mainly due to its natively support for a wide range of image formats. However, there are medical imaging modalities (e.g. endoscopy, ultrasound), with video output formats that are still not supported by ImageJ (e.g. VOB, MPG). With the base package of ImageJ it is possible to open videos in AVI format1 and with additional plugins (e.g., QuickTime Movie Writer2, JMF Movie Reader3, QuickTime Opener4) videos in Quicktime Movie format (i.e. MOV and PIC) are also supported. For other video formats it is necessary to convert the video to a supported format using a third party video converter application. A video is basically a temporal sequence of images. An average endoscopy produces a five to ten minute video with a frame rate of 50 fps. Of these tens of thousands of images only a few are relevant, thus it is necessary to select and extract the relevant images to be analyzed / processed in ImageJ. In this paper, we present an ImageJ plugin developed to select and extract frames from video in diverse formats (e.g. MOV, AVI, VOB, MPG, MP4, FLV, MKV). Its user interface allows for video viewing and browsing. During video visualization the user can grab frames and export them as images or an Image Stack to ImageJ. This plugin, entitled “Multi-format Video Frame Grabber - MVFG” was developed using the vlcj framework (a Java framework for the vlc media player)5.